2012
DOI: 10.1007/s10530-012-0328-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the non-native amphibian species Discoglossus pictus on the recipient amphibian community: niche overlap, competition and community organization

Abstract: The painted frog, Discoglossus pictus, was introduced into the Iberian Peninsula 100 years ago and its distribution has steadily increased since then. We studied the effects of this non-native amphibian species on the native ones in the northeastern area of the peninsula. We compared amphibian assemblages in regions with and without D. pictus to estimate niche overlap between species. Additionally, we carried out a laboratory evaluation of the effects of competition between the non-native and the two native sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 87 publications
2
26
0
Order By: Relevance
“…, Richter‐Boix et al. ). The shift may be explained by competition resulting in lowered species richness in localities invaded by house mice, which can translate into fewer opportunities for native species to co‐occur.…”
Section: Discussionmentioning
confidence: 99%
“…, Richter‐Boix et al. ). The shift may be explained by competition resulting in lowered species richness in localities invaded by house mice, which can translate into fewer opportunities for native species to co‐occur.…”
Section: Discussionmentioning
confidence: 99%
“…The essentially carnivorous D. galganoi (Richter‐Boix et al. , Arribas et al. ) performed a potentially maladaptive shift toward higher herbivory in the early spring heat wave, as suggested by the low mass at metamorphosis when compared to strictly carnivorous tadpoles.…”
Section: Discussionmentioning
confidence: 99%
“…Blaustein et al (2011) argued the importance of researching amphibian declines at the community level and investigating synergistic effects of multiple stressors instead of focusing on single factors. In recent studies, Richter-Boix et al (2013) compared invaded and non-invaded amphibian populations on the Iberian Peninsula to test whether the introduction of Painted Frog (Discoglossus pictus) altered communities. They found that the presence of D. pictus compromised species co-occurrence patterns at the regional scale.…”
Section: Reviewsmentioning
confidence: 99%